(untitled) (Bangladesh Heart Journal, 2018)
Native arterio-venous fistula (AVF) are the preferred mode of repeated vascular access for the chronic renal failure patients surviving on hemodialysis because of their easy accessibility, good long term patency, low complication rate and cost-effectiveness. Creation of a fistula between the radial or brachial artery and a suitable adjacent vein is the most commonly practiced option. However the major upper arm veins of the CKD patients are often found thrombosed, cord like and not suitable for AV anastomosis. A 48 years old male patient of chronic kidney disease with a permanent catheter placed in the right subclavian vein was referred to create an AV fistula. On exploration none of the upper limb veins was found suitable for fistula formation. The proximal part of the left GSV was harvested from patient’s left upper thigh and was used to make a connection between left brachial artery at cubital fossa and the left axillary vein. To avoid over flooding of the limb vasculature, partial banding of the left axillary vein was done distal to this anastomosis. When all options in both upper limbs are exhausted, autologous great saphenous grafts may be a very useful tool for the surgeons in creating upper limb AV fistulas in difficult situations Bangladesh Heart Journal 2018; 33(2) : 134-137